PENGARUH METODE ROLE PLAYING DALAM PEMBELAJARAN FIKSI DAN PENERAPAN KURIKULUM MEREDEKA PADA SISWA KELAS VII SMP ALFADLLU - Uswatun Khasanah; Hany Uswatun Nisa; Ghufroni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the effect of the role-playing method in fiction learning and its implementation within the Merdeka Curriculum for seventh-grade students at SMP Alfadllu. Fiction learning requires an innovative approach to help students deeply understand and internalize characters and plotlines. The role-playing method is believed to enhance active student engagement and contextual understanding of concepts. This study employs a quantitative approach with a quasi-experimental design. The research population includes all seventh-grade students at SMP Alfadllu, with the sample selected using a purposive sampling technique. Data were collected through a fiction comprehension test instrument and a student response questionnaire regarding the role-playing method. Data analysis was performed using SPSS (Statistical Product and Service Solutions) via hypothesis testing in the form of an independent sample t-test to determine differences in learning outcomes between the experimental group (which used the role-playing method) and the control group (which used conventional methods). Results of the study showed that the role-playing method had a positive impact, leading to an 18.87% increase in fiction comprehension among seventh-grade students at SMP Alfadllu. This was observed by comparing the scores of the experimental group with the conventional learning methods used in the control group. Furthermore, the implementation of this method aligns with the principles of the Merdeka Curriculum, which emphasizes differentiated and student-centered learning. These findings indicate that the role-playing method is effective in improving the quality of fiction instruction and supports the achievement of the Merdeka Curriculum's goals.